DISTRIBUTION OF ELEMENTAL AND ORGANIC CARBON AEROSOLS IN THE ATMOSPHERE BETWEEN JAPAN AND ANTARCTICA - ニシカワ, マサタカ; カナモリ, サトル; カナモリ, ノブコ; ミゾグチ, ツグオ; ムラヤマ, ショウヘイ; アオキ, シュンジ; カワグチ, サダオ; NISHIKAWA, Masataka; KANAMORI, Satoru; KANAMORI, Nobuko; MIZOGUCHI, Tsuguo; MURAYAMA, Shohei; et al. (National Institute of Polar Research, 1991)
P(論文) During the period from November to December, 1988,aerosol samples were collected on board the research vessel "SHIRASE" between Japan and Antarctica. Carbon contents of the samples were determined using gas chromatography, after separating elemental and organic carbon by the conventional pyrolysis method. The concentration levels of elemental and organic carbon aerosols were found to be on the order of 100ng/m^3 over the Antarctic Ocean. These values were lower by two orders of magnitude than those in Tokyo Bay and higher by one order of magnitude than those at Syowa Station, Antarctica. departmental bulletin paper